Knowledge sharing behaviors among non academic staff of higher learning institutions: attitude, subjective norms and behavioral intention embedded model - Rahman, Muhammad Sabbir; Osman Gani, Aahad M; Mat Daud, Nuraihan; Fadi Abdel, Muniem Abdel Fattah (Emerald Group Publishing Limited ., 2016)
Purpose – This paper aims to develop and combined an understanding of the antecedents of knowledge sharing behavior among the non-academic staff of different higher learning institutions in Malaysia. Design/methodology/approach – The researchers tested the hypotheses from the survey data from the non-academic staff of different private and public higher learning institutions in Malaysia. This research also applied confirmatory factor analysis and structural equation modeling to examine the proposed hypothesis of this inquiry. Findings – The results indicate that attitude and subjective norms both influence the staff knowledge sharing behavior significantly and positively. Additionally, this research also revealed that intention of knowledge sharing variable plays a substantial role as a mediating variable in those relationships. Research limitations/implications – This research is a cross-sectional survey. As a result, the limited sample size in this study may affect the power of generalizability. Further research may prove the model across different times to respect the nature of the knowledge sharing behavior among the non-academic staff of higher learning institutions. Practical implications – The results of this research clearly explain how academic institutions may proceed for knowledge sharing culture in their respective department by considering the variables used in this inquiry. If the office of any academic institution feels that the knowledge sharing among the non-academic staff is still low, they can utilize the factors as a tool to facilitate the advancement of the knowledge sharing environment in their respective sections. Originality/value – Previous research primarily focuses on the knowledge sharing behavior of students and lectures’ perspective. This research minimizes the gap by including the non-academic staff of higher learning institutions. In summation, this research also examined the mediating role of knowledge sharing intention in the relationship between attitude, subjective norms and knowledge sharing behavior.